The Role of Gamification as an Intervening Variable in the Influence of Digital Competence and Work Flexibility on the Performance of Gig Logistics Workers in Semarang City (Pusat Riset dan Inovasi Nasional, 2026)
The development of the digital economy has led to an increase in the number of gig workers in the logistics sector, including in the city of Semarang. However, work flexibility, as a key feature of the gig system, has not been fully able to optimize worker performance. The phenomena of long working hours, fatigue, and performance differences between workers indicate that digital competence and work flexibility require supporting mechanisms that can increase work engagement. In this context, gamification on digital logistics platforms is seen as a strategic approach to increase the motivation and performance of gig workers. This study aims to analyze the effect of digital competence and work flexibility on the performance of logistics gig workers in Semarang City with gamification as an intervening variable. The study uses a quantitative approach through a survey method of logistics gig workers, with data analysis using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The population consists of 128 online driver workers operating in the city of Semarang. The sampling technique used is purposive random sampling. The results of the study indicate that digital competence has a positive and significant effect on the performance of gig logistics workers, while work flexibility has a positive and significant direct effect on the performance of gig logistics workers. Gamification has been proven to have a positive effect on performance and is able to mediate the influence of digital competence and work flexibility on the performance of logistics gig workers. These findings emphasize the importance of continuous gamification implementation in order to optimize the performance of logistics gig workers in the digital economy era.